Ichthyofauna of Lake Buaya, South Sulawesi: Iktiofauna Danau Buaya, Sulawesi Selatan - Andy Omar, Sharifuddin; Parore, Rostiani; Rahim, Sri Wahyuni; Parawansa, Basse Siang; Umar, Moh. Tauhid (Habitus Aquatica, 2020)
Lake Buaya is one of the lakes located in the central part of South Sulawesi. Information about ichthyofauna biodiversity in this lake does not yet exist. Therefore, this study was conducted to analyze species composition, relative abundance, diversity index, evenness index, and dominance index, fish caught in the waters of Lake Buaya. This research was conducted in March to May 2019. Sampling was carried out four times over two months using a fishing gear with a mesh size of 2 inches. Sample analysis was carried out at the Fisheries Biology Laboratory, Faculty of Marine Sciences and Fisheries, Hasanuddin University. During the study 328 fish were found that belong to 12 species and 9 families. The highest abundance of individuals and relative fish abundance was found in Trichopodus pectoralis (snakeskin gourami). The range of diversity index, evenness index, and dominance index were 2,11–2,35, 0,85–0,95, and 0,10–0,15, respectively.